ii DISPERSION ANALYSIS OF THE WATER VAPOR EMISSION OF GEOTHERMAL ENERGY POWER PLANTS USING CALPUFF (Case Study PT Pertamina Geothermal Energi Lapangan Kamojang Cooling tower) - RIFKI MUKTI (NIM :12809027);Pembimbing :Drs. Zadrach L. Dupe, M.Sc , BRAMUDYA
This study intends to identify the distribution pattern of water vapor from the cooling tower of PT Pertamina Geothermal Energy located in West Java with altitude about 1500 meters above sea level. The distribution pattern is divided into four different months i.e. January, April, July, and October. The period of the distribution is based on the monsoonal activity that occurred in Indonesia, especially Java. Each month simply spreading the pattern observed for one week. Distribution pattern observed using CALPUFF. CALPUFF is a multi-layer, multi-species distribution models of non-steady-state puff that can simulate the effects of time and space variations of meteorological conditions on the propagation, transformation, and transfer of pollutants. CALPUFF requires the results of the wind field model from CALMET. Based on the results of verification model, CALMET is able to provide wind field with correlation values > 0,5 and error < 1 m/s every week at the observation point. Dominant wind direction in every week in the different month affected by the monsoon season took place in Indonesia. Southwest monsoon season which takes place on Desember-Januari-February. East monsoon season which takes place on June-July-August. Decision on AWSÃ‚Â’s radius data effect will influence CALMET. The difference range will influence the wind field and the distribution of water vapor concentration. Distribution of water vapor concentration largely followed the direction in which the wind blows. The highest concentration of water vapor every hour that occurs in the first week of April, July, October, and January is 80 g/m3, 71g/m3, 85 g/m3, and 75 g/m3 which were around cooling tower.